Determination of acid-base status in working mules - Trujillo Martínez, Valeria (2019)
A descriptive study was conducted to describe acid-base alterations in working mules. Blood samples of 29 mules were analyzed and data was interpreted both by the traditional approach (Henderson-Hasselbach) and the Simplified Strong Ion Difference (Stewart). The parameters evaluated were pH, pCO2, HCO3 -, excess of base, difference of strong ions, total concentration of non-volatile buffer anions and blood lactate. Results showed that 48.3% of the individuals presented at least one acid-base disorder by the traditional approach, while 20.7% did so by the Stewart’s approximation. The alterations most commonly presented were metabolic alkalosis (20.7%), respiratory alkalosis (13.8%), hyperlactatemia alkalosis (10.3%) and strong ion acidosis (17.2%). The results between the two approaches did not show a coincidence. In conclusion, the acid-base alterations in the working mules may be due to factors such as overwork, relative humidity and the environmental temperature, which lead to marked electrolyte losses, and the absence of supplementation of mineral salts in the diet of animals.